Major Streams in the Economics of Inequality: A Qualitative and Quantitative Analysis of the Literature since 1950s - Pedro G. Lima; Pedro N. Teixeira; Sandra T. Silva (Institute of Labor Economics (IZA), 2021)
Since the late twentieth century there has been a growing interest in academic and political circles on inequality. In this paper, we develop a systematic analysis of the literature on this topic published in economic journals since the 1950s. This is done through an innovative approach that presents (i) an identification and characterization of the main streams of research about Inequality since the 1950s; (ii) the development of a new method of analysis that combines (ii-a) a quantitative bibliometric analysis using the VOSviewer software, which maps them into different clusters, (ii-b) a qualitative analysis, where we determine the main streams of research, based, not only on the content of each reference, but also on the context where they are cited, and provide context to the development of each cluster by analysing the most important journals, authors, and institutions. The analysis leads to the identification of seven clusters, each of them with several streams of research. Each of the clusters is characterized according to several aspects such as the journals where the contributions were published, the alma matres and academic affiliations of the authors, and the countries in which those authors are based. The leading journals and the dominant academic institutions are the same as found in economics broadly considered, but they vary from cluster to cluster. Among the authors that have had major influence in the development of this field of economic research, stand out Anthony Atkinson, Simon Kuznets, Michael Kalecki, and Thomas Piketty.
Keywords: B2; D31; E24; 330; inequality; distribution of income; wealth; bibliometrics; Kuznets; Atkinson; Piketty; Kalecki